Factors That Trigger Students Studying at Higher Educational Institutions in Azerbaijan 1 to Involve in Cheating in Exams and Assignments - Suleymanov, Suleyman (ADA University, 2022)
This study, based on a qualitative interview approach, aimed at exploring factors triggering students studying in higher educational institutions in Azerbaijan to engage in cheating in the exams and assignments. Although there are a great deal of measures taken against cheating at higher educational institutions in Azerbaijan still there are many cheating cases among the students. The research study explored the following research questions: What are students’ perceptions about cheating? What triggers students studying at Azerbaijani higher educational institutions to cheat in the exams and assignments? In order to explore the above mentioned research questions students studying in higher educational institutions in Azerbaijan were recruited and interviewed through semi-structured interviews. The investigation took place in 2022 and the collected data were coded and later divided into four categories. The methodology and discussion of the study findings with the literature review was also provided in the final sections.
Keywords: Education, Higher -- Azerbaijan.; Education, Higher -- Azerbaijan -- Challenges.; Education, Higher -- Cheating.; Education